2017
DOI: 10.4236/ajc.2017.52009
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mobile Phones for Economic Development in Cameroon

Abstract: Research concerning mobile phones and economic development in Africa has undergone rapid growth in recent years. This paper evaluates the rate at which Cameroonians use mobile phones to carry out their day-to-day business transactions and to a larger extent, investigate the type of business development brought about by mobile phones. It measures the extent to which mobile phones have enhanced business transactions among traders. In all, 100 questionnaires were administered on a face-to-face basis to business p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…This innovation can help to reach those who do not have access to banking services and thus improve financial inclusion [22]. Ngange and Beng [19] and Chimaobi and Chizoba [31] demonstrated that mobile commerce facilitates communication between users. The later scholars went further to show that the platform improves the efficiency of the business operations.…”
Section: Mobile Money and Smesmentioning
confidence: 99%
See 4 more Smart Citations
“…This innovation can help to reach those who do not have access to banking services and thus improve financial inclusion [22]. Ngange and Beng [19] and Chimaobi and Chizoba [31] demonstrated that mobile commerce facilitates communication between users. The later scholars went further to show that the platform improves the efficiency of the business operations.…”
Section: Mobile Money and Smesmentioning
confidence: 99%
“…In Cameroon, it is the State that made an effort by opening a bank for the SMEs in July 2015 [44]. However, even if the MNOs cannot offer microcredit in Cameroon, it is perceived by many scholars that the mobile money services facilitate the commercial dealings for SMEs [19,31]. According to Ngaruiya et al [10] and Amponsah [21], the rapid diffusion of mobile money transfer is seen as a potentially vital tool for facilitating financial transactions.…”
Section: Mobile Money and Smesmentioning
confidence: 99%
See 3 more Smart Citations